Bridging Cultures for Global Environmental Sustainability: Empowering Change through Higher Education and Beyond - Aboukhousa, Heba; AlKamali , Waheeb; Eljattari , Belkacem (Journal of Ecohumanism, 2024)
Addressing environmental challenges and taking meaningful action on climate change is becoming more critical every day. This paper explores how embracing cultural diversity can lead to better solutions for these pressing issues. When people from different backgrounds share ideas and work together globally, new ways to support both climate action and sustainability can emerge. The paper starts by looking at basic ideas about sustainability and explains why we need to act on climate change now. It also explores how collaboration between different cultures can help solve environmental issues. Examples such as the Paris Agreement, the Great Green Wall, and the integration of indigenous knowledge demonstrate how diversity enhances global sustainability initiatives. Promoting awareness and providing education are essential to motivating broader participation in sustainability efforts. The paper also addresses challenges like political conflicts, economic interests, and different beliefs. By focusing on inclusion and cooperation, it suggests we can overcome these barriers. The main message is clear: diversity makes climate action stronger, and by working together, we can build a healthier, more sustainable world for everyone.